The Role of Teachers in Shaping the Character of Fourth Grade Students at SDN Ululere Elementary School, Bungku Timur Subdistrict, Morowali Regency - Bayu Lasmana; Nashrullah Nashrullah; Sisriawan Lapasere; Zulnuraini Zulnuraini; Dyah Rahmawati; Noor Alfulaila (FKIP - Universitas Riau, 2026)
Character education plays an important role in shaping the personalities of elementary school students. This study aims to analyze the role of teachers in shaping the character of fourth-grade students at SDN Ululere. The research method used is descriptive qualitative with data collection through observation, interviews, and documentation. The results show that teachers play the role of educators, teachers, and coaches in shaping students' character. As educators, teachers instill religious values and responsibility through habitual prayer, exemplary behavior, and routine activities such as class duty. As teachers, teachers integrate character values into learning through group discussions and differentiated learning, emphasizing honesty, cooperation, and responsibility. As coaches, teachers provide personal guidance, routine religious activities, and training in student independence. From this character-building process, four main characters are strengthened, namely religious, honest, independent, and responsible. This study confirms that character building in students requires a collaborative approach between teachers, schools, and parents in a consistent and sustainable manner.